Potassium release during pulverized biomass combustion in a tubular burner investigated by TDLAS. (1st June 2022) - Cen, Sun; Xiaolin, Wei; Teng, Li; Li, Zhou; Qinzheng, Teng; Sen, Li
Highlights: The release of potassium from rice husk's combustion in a tubular burner was investigated. Potassium release process was monitored online using calibration-free TDLAS. The release characteristics of different occurrences of potassium metals in a turbulent environment were discussed. The effect of turbulent oxy-fuel atmosphere on the release of different occurrence forms of potassium is discussed. The potassium release characteristics of biochar combustion metals in a turbulent environment were discussed. Abstract: The ignition and effect of different treatments of pulverized biomass on potassium release were monitored online using visible light detection and calibration-free TDLAS techniques in a tubular burner, with the following main conclusions. High-speed cyclonic flow enhanced the transport effect around the particles, allowing for the rapid separation and diffusion of volatile fractions from biomass particles, as well as the rapid but transient release of potassium. There were no visible envelope flames or trailing flames around the burning particles. High-speed photography also confirmed the homo-heterogeneous ignition. The release of water-soluble potassium was significantly postponed under an O2 /CO2 atmosphere compared with the air atmosphere, shifting from a quick and instantaneous model to a continuous and slow-release one. In comparison, the O2 /CO2 atmosphere had little suppression effect on the exchangeable and organic potassium release process. In both air and O2 /CO2 combustion, the water-soluble potassium release was the fastest, followed by organic potassium and exchangeable state potassium. The release ratio of atomic potassium, the proportion of released atomic potassium in initial total potassium in particles, from water-washed and NH3 Ac-washed rice husk is higher than that from rice husk combustion, under O2 /CO2 and O2 /N2 combustion conditions. The release process of potassium enriched in char takes a long time but has a low release rate. The inhibitory effect of the O2 /CO2 atmosphere on the potassium release during rice husk char combustion was relatively weak compared with rice husk combustion.